“КЕЙС-СТАДИ” МЕТОДИНИ ФИЗИКА ФАНИГА ҚЎЛЛАШНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
The article analyzes the features of drawing physical tests up, as well as the application of the case method in the teaching of physical sciences.